A library of recombinant Babesia microti cell surface and secreted proteins for diagnostics discovery and reverse vaccinology. Issue 2 (February 2019) - Elton, Catherine M.; Rodriguez, Marilis; Ben Mamoun, Choukri; Lobo, Cheryl A.; Wright, Gavin J.
Graphical abstract: Highlights: An open resource of recombinant Babesia microti cell surface and secreted proteins. Proteins are expressed in a mammalian expression system and are immunoreactive. Concordance of immunoreactive proteins in sera from infected humans and mice. Proteins will be useful for diagnostics, vaccines and host-pathogen interactions. Abstract: Human babesiosis is an emerging tick-borne parasitic disease and blood transfusion-transmitted infection primarily caused by the apicomplexan parasite, Babesia microti . There is no licensed vaccine for B. microti and the development of a reliable serological screening test would contribute to ensuring the safety of the donated blood supply. The recent sequencing of the B. microti genome has revealed many novel genes encoding proteins that can now be tested for their suitability as subunit vaccine candidates and diagnostic serological markers. Extracellular proteins are considered excellent vaccine candidates and serological markers because they are directly exposed to the host humoral immune system, but can be challenging to express as soluble recombinant proteins. We have recently developed an approach based on a mammalian expression system that can produce large panels of functional recombinant cell surface and secreted parasite proteins. Here, we use the B. microti genome sequence to identify 54 genes that are predicted to encode surface-displayed and secreted proteins expressed during the blood stages, and show that 41 (76%) are expressed using our method at detectable levels. We demonstrate that the proteins contain conformational, heat-labile, epitopes and use them to serologically profile the kinetics of the humoral immune responses to two strains of B. microti in a murine infection model. Using sera from validated human infections, we show a concordance in the host antibody responses to B. microti infections in mouse and human hosts. Finally, we show that BmSA1 expressed in mammalian cells can elicit high antibody titres in vaccinated mice using a human-compatible adjuvant but these antibodies did not affect the pathology of infection in vivo. Our library of recombinant B. microti cell surface and secreted antigens constitutes a valuable resource that could contribute to the development of a serological diagnostic test, vaccines, and elucidate the molecular basis of host-parasite interactions.